Histomorphogical and Histochemical Studies on Sperm Storage Tubules in Japanese Quail - Sukhadeve, S.V. (Indian Journal of Veterinary Anatomy, 2019)
The present work was conducted on oviduct of 42 Japanese quails from 8 weeks to 32 weeks of age to study the histological and histochemical aspects of sperm storage tubules located at uterovaginal junction. The sperm-storage tubules (SST) were observed as branched slightly coiled structures extending into the lamina propria from the base of the mucosal folds. These appeared as darkly stained tubular glands in between the proprial glands and were abundant at the uterovaginal junction than infundibulo-magnum junction. Their number and size increased with the increase in age of bird. SST had proximal and distal parts; the proximal part was lined by pseudostratified columnar epithelium and distal part by non-ciliated simple columnar epithelium. Abundance of collagen fibres were observed in the interglandular tissue. Histochemical studies revealed strong to intense reaction of acid and neutral mucopolysaccharides, moderate for lipids and weak reaction for basic proteins in SST.